MÉTODO DE OBJETIVOS PARA INTEGRAÇÃO DE PONTOS DE VISTA EM ENGENHARIA DE REQUISITOS DE COMÉRCIO ELETRÔNICO - LOBATO FILHO, Ozéas Rodrigues (2004)
In this work, we cited the existent methods for viewpoint together with a comparative study among them, we identify the types of requirements viewpoints that the existing methods are using. Soon after we present one method that is based on value for viewpoint in e-business, mentioning its framework which we incorporate in our method in e-business to show the technical and commercial viability of the idea. We will show that needs and interests of several stakeholders types that can be expressed through different viewpoint models. We propose an extension of Use Case Maps (UCMs) for e-business together with the Goal based Requirements Analysis Method (GBRAM), as a method of Requirements Engineering to reach the integration of the necessary point of view. Besides, It is showing that the method of objectives is used in the elicitation and analysis of e-business requirements. A case study of commerce in electronic publicity is used to illustrate our method.